2004
DOI: 10.1126/science.1103350
|View full text |Cite
|
Sign up to set email alerts
|

Multicompartment Micelles from ABC Miktoarm Stars in Water

Abstract: By combining three mutually immiscible polymeric components in a mixed-arm star block terpolymer architecture, we have observed the formation of a previously unknown class of multicompartment micelles in dilute aqueous solution. Connection of water-soluble poly(ethylene oxide) and two hydrophobic but immiscible components (a polymeric hydrocarbon and a perfluorinated polyether) at a common junction leads to molecular frustration when dispersed in aqueous solution. The incompatible hydrophobic blocks form cores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
890
2
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 954 publications
(927 citation statements)
references
References 26 publications
28
890
2
4
Order By: Relevance
“…This step is quite crucial for the preparation of welldefined target miktoarm star polymer due to the possible click coupling of 2 by (N 3 ) 2 ANH. The presence of coupling product, PEG-NH-PEG, will lead to the formation of Y-shaped AB 2 product, PNIPAM-b-(PEG) 2 . In designing the reaction, the molar ratio of (N 3 ) 2 ANH to alkynyl moieties of 2 was fixed at 50:1.…”
Section: Synthesis Of Abc Miktoarm Star Terpolymermentioning
confidence: 99%
See 1 more Smart Citation
“…This step is quite crucial for the preparation of welldefined target miktoarm star polymer due to the possible click coupling of 2 by (N 3 ) 2 ANH. The presence of coupling product, PEG-NH-PEG, will lead to the formation of Y-shaped AB 2 product, PNIPAM-b-(PEG) 2 . In designing the reaction, the molar ratio of (N 3 ) 2 ANH to alkynyl moieties of 2 was fixed at 50:1.…”
Section: Synthesis Of Abc Miktoarm Star Terpolymermentioning
confidence: 99%
“…[1][2][3][4] The first few examples of the preparation of ABC miktoarm star terpolymers exclusively employed anionic polymerization, relying on the strict control of molar ratios between reactive species. [5][6][7][8][9][10][11][12][13] With the advent of controlled radical polymerizations, such as nitroxide-mediated radical polymerization (NMP), atom transfer radical polymerization (ATRP), and reversible addition-fragmentation chain transfer (RAFT) polymerization, the once challenging task of synthesizing ABC Correspondence to: S. Liu (E-mail: sliu@ustc.edu.cn) miktoarm star polymers has been rendered much easier.…”
Section: Introductionmentioning
confidence: 99%
“…Low polarizibility of fluorine results in weaker dispersion forces between fluorocarbon tails as compared with hydrocarbons, which causes fluorocarbon chains being both hydrophobic and lipophobic [8]. Co-assembly of FS with hydrocarbon amphiphiles can lead to multicompartment structures in which fluorinated chains form segregated domains [9].…”
Section: Introductionmentioning
confidence: 99%
“…They showed quite different microdomain morphologies in bulk [19][20][21] and self-assembly behavior in solution 22,23 compared with the comb-shaped, 24 block-grafted, 25,26 cyclic, 27,28 arborescent, 29 and hyperbranched 30 copolymers. In the investigation of ABC 3-miktoarm star-shaped terpolymers polystyrene-poly(ethylene oxide)-poly(ethoxyethyl glycidyl ether) (PS-PEO-PEEGE), 31 it was found that the hydroxyl end group of PEEGE block could be modified further, and then the miktoarm star copolymers with functional group as alkyne group were obtained.…”
mentioning
confidence: 99%